The Mandatory Trade Union Contribution Of The Statutory Public Server Under The Perspective Of Tax Legality - Daniela Ramos de Oliveira dos Santos; Antônio Carlos Diniz Murta (Revista de Direito Administrativo e Gestão Pública, 2016)
The article proposes the discussion of tax legality in the face of IN No 01/2008 of the MTE which extended compulsory union dues of art. 149 of CF / 88 and art. 578-591 of the Labor Code for statutory civil servants . It discusses the origin and nature of compulsory union dues under the tax legality of art. 150, I, CF / 88 and the seal of the analogy in Tax Law when dealing with major tax requirement (art. 108, § 1 of CTN ) . It started from the hypothesis that the IN 01/2008 MTE is illegal , since the main tax obligation arises from law.